2022
DOI: 10.3389/fonc.2022.1076267
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a radiogenomics model to predict axillary lymph node metastasis in breast cancer integrating MRI with transcriptome data: A multicohort study

Abstract: IntroductionTo develop and validate a radiogenomics model for predicting axillary lymph node metastasis (ALNM) in breast cancer compared to a genomics and radiomics model.MethodsThis retrospective study integrated transcriptomic data from The Cancer Genome Atlas with matched MRI data from The Cancer Imaging Archive for the same set of 111 patients with breast cancer, which were used as the training and testing groups. Fifteen patients from one hospital were enrolled as the external validation group. Radiomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Combining different data modalities usually leads to better performance. Therefore, such an approach should be more extensively researched in future studies to provide optimal models for breast cancer lymph node classification [ 9 , 50 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining different data modalities usually leads to better performance. Therefore, such an approach should be more extensively researched in future studies to provide optimal models for breast cancer lymph node classification [ 9 , 50 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…An interesting study by Chen et al combined DCE-MRI radiomics data with transcriptomic data from The Cancer Genome Atlas for a set of 111 patients with breast cancer [ 50 ]. Another fifteen patients were enrolled for the external validation group.…”
Section: Studies Combining Radiomics and Clinicopathological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the study by Fan et al 49 in 2022, a radiomic model was built to predict prognosis of breast cancer using the Oncotype DX Recurrence Score, and another study by Woodard et al 50 showed the relationship between BI-RADS-based features and the Oncotype DX Recurrence Score. Additionally, another study by Chen et al 51 in 2022 showed that models combining radiomic and genomic features performed better than radiomic models or genomic models alone in predicting ALNM of breast cancer. Radiogenomics has been applied to predict the TME in several types of solid tumors but not breast cancer.…”
Section: Radiomic Studies Regarding the Tme Reveal Crucial Biomarkers...mentioning
confidence: 99%
“…Multitype studies based on radiomics and/or deep learning features have been conducted to evaluate LNM in breast cancer. For example, in one multi-center study, a radiogenomics model combining radiomics features and genomics features improved the performance of predicting LNM in breast cancer [ 8 ]; in another based on 110 MRI images from a single center, potential pathways for the genetic mechanism of deep learning imaging phenotypes were identified [ 9 ]. The biological significance of the radiomics feature phenotype had been analyzed in multiple studies, but deep learning feature phenotypes were only identified during the image recognition process, and the quantification of specific features was not mentioned.…”
Section: Introductionmentioning
confidence: 99%